Phenotypic and Serotypic Characterization of Staphylococcus aureus Strains from Subclinical Mastitis Cattle (KARAKTERISASI SECARA FENOTIPE DAN SEROTIPE STAPHYLOCOCCUS AUREUS YANG BERASAL DARI MASTITIS SUBKLINIK PADA SAPI) - Ningrum, Siti Gusti; Arnafia, Wyanda; Oscarina, Sylvia; Soejoedono, Retno Damajanti; Latif, Hadri; Ashraf, Mohammad; Wibawan, I Wayan Teguh (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
Staphylococcus aureus is known as a major causative agent of mastitis in dairy cattle. In the presentstudy, 104 isolates of Staphylococcus originated from subclinical mastitis cattle characterized for thephenotypic properties and the presence of Staphylococcal protein A (Spa). Some bacteria were resistancesagainst several antibiotics were also studied, such as erythromycin, streptomycin, tetracycline, cefepime,nitrofurantoin, amikacin, chloramphenicol, and ciprofloxacin. About 78% of the isolated were moderatelysensitive to nitrofurantoin, while 89% were highly resistant to cefepime and ciprofloxacin. Using thevarious mammals’ sera, seven isolates out of 104 revealed the presence of Spa.
Keywords: protein A; Staphylococcus aureus; subclinical mastitis; phenotyping